The Role of Neck Ultrasonography and Nuclear Imaging in the Diagnosis of Congenital Hypothyroidism - Soundararajan Sumathy; Sengottaiyan Palanivel; Kethipalli Nagaraju; Chidambaram N. B. Harisankar; Jeyaraj Ashokraja; Jayachandran Senthilkumar; Palaniyappan Sreenivasan; Subbiah Sridhar (Indian Journal of Endocrinology and Metabolism)
Introduction: Congenital hypothyroidism (CH) is the most common preventable cause of mental retardation, and the two important causes of CH are thyroid dysgenesis and dyshormonogenesis. Thyroid imaging is an integral part of identifying the specific aetiology of CH. We aimed to study the aetiological profile of CH and compare the imaging findings of ultrasonography (USG) and nuclear scintigraphy. Methods: It is a prospective, cross-sectional study conducted over 3 years. The clinical, USG, and technetium-99 m (99 mTc) scintigraphy reports of CH children were analysed. Results: Sixty-two CH children were included in the study with an equal male-to-female ratio (1.1:1). There was a significant association between parental consanguinity and CH observed in 35.5% of cases (P = 0.006). In USG neck, 44 (71%) had normal and/or enlarged thyroid glands at the eutopic location, 16 (27.4%) cases had an absent gland, and ectopic as well as hypoplastic unilateral gland was observed in one (1.6%) each. Among 35 children, who underwent scintigraphy, 12 (34.3%) had absent uptake, 4 (11.4%) had ectopic uptake, and 1 (2.8%) child had unilateral normal uptake. The remaining 18 (51.5%) children, whose scintigraphy showed normal or avid uptakes, were diagnosed with dyshormonogenesis. Three cases were diagnosed as apparent athyreosis. Conclusion: Dyshormonogeneis is the more commonly observed etiology of CH as compared to thyroid agenesis in the present study. A combined imaging approach with scintigraphy and USG is needed to delineate the specific etiology of CH. We need long-term Indian data to know the paradigm shift in the etiological pattern of CH as compared to Western studies.